Improvement of antioxidant status on adults obesity after intervention antioxidant drinks. (November 2018) - Hasan, M; Damayanthi, E; Anwar, F
Abstract: Obesity will increase the risk of oxidative stress that can lead to metabolic syndrome. Antioxidant foods have known benefits in improving the antioxidant activity and inhibiting oxidation reaction in the body. Tomato and rice bran are functional foods containing high antioxidant compounds specifically lycopene in tomato and oryzanol in rice bran. The purpose of study was to analyze the effect of the drinks of tomato extract, rice bran powder and rice bran oil emulsion to antioxidant activity. The design of this study used was quasi-experimental study with two groups pre and posttest. The 26 subjects were divided into 2 groups, each group has 13 subjects with purposive sampling. Intervention conducted for 28 days that each group was given 2 cups @220 ml tomato extract per day for 14 days and then continue as group A given 2 sachets (30 g) of flavored-rice bran powder and as group B given 2 cups @ 220 ml rice bran oil emulsion drink during 14 days. The analysis of activity antioxidant used was MDA and DPPH methods. The results of paired t test analyzed showed that intervention could decrease MDA levels significantly in group B (p = 0.03) and AEAC in group A and B (p = 0.00). Intervention products are improve level of antioxidant subjects.